Urban redevelopment, the new logics of expulsion, and individual precarity in Kleber Mendonça Filho’s Aquarius and Aravind Adiga’s Last Man in Tower - Mendes, Ana Cristina Ferreira (2019)
Drawing on Kleber Mendonça Filho's film Aquarius (2016) and Aravind Adiga's novel Last Man in Tower (2011), this article is concerned with the impact on individuals and communities of forms of impersonal, systemic violence resulting from neoliberal accumulation and the reproduction of mobile capital, extending existent precarities as well as opening up new precarities. We examine the experiences of the previously less precarious-that is, members of the middle classes in Recife, Brazil, and Mumbai, India-now rendered newly precarious. We frame the temporality of these precarities via themes of memory, presentism and futurity in order to depict how sites in the Global South are targeted by mobile capital, and how individuals and communities are impacted by the growing extent of precarities, eroding long-established systems of social and communal protection, and undermining social loyalties and securities. Through the narratives of a novel and a film, we analyse cultural representations of redevelopment projects as epitomes of frictionless, mobile capital. Such capital has the effect of increasing the precarity of individuals, which in turns frays the bonds of communities, heightening network and community precarities. This selection is grounded in Jacques Rancière's argument that '[f]iction is at work whenever a sense of reality must be produced' and interrelatedly in the critical space offered by the interpenetration between fiction, political life and the construction of social realities. Engaging with the fictional situations depicted in Aquarius and Last Man in Tower adds to the understanding of what happens in the lifeworld when residents are thrown into a condition of sudden and acute precarity when coerced to evacuate their long-time homes as a result of redevelopment projects, and in particular the pressures faced by the last individuals standing, especially when they speak truth to power.